2021
DOI: 10.1186/s40001-021-00578-8
|View full text |Cite
|
Sign up to set email alerts
|

A first case report of nasopharyngeal Mycobacterium abscessus subspecies massiliense infection

Abstract: Background Mycobacterium abscessus subspecies massiliense is a non-tuberculous mycobacteriosis and was subdivided from Mycobacterium abscessus in 2006. This article is the first report on nasopharyngitis caused by Mycobacterium abscessus subspecies massiliense. Case presentation A 45-year-old woman had an 18-month history of recurrent nasopharyngitis and presented with pain in the throat. Mycobacterial tissue culture and polymerase chain reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Of the three patients with pharyngeal infection, our patient and that reported by Oki et al 12 had a history of physical irritation of the pharynx caused by nasal irrigation and nasopharyngeal abrasive therapy, respectively. Among the five patients with laryngeal lesions only, four had a history of steroid therapy, and two were administered with inhaled steroids.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…Of the three patients with pharyngeal infection, our patient and that reported by Oki et al 12 had a history of physical irritation of the pharynx caused by nasal irrigation and nasopharyngeal abrasive therapy, respectively. Among the five patients with laryngeal lesions only, four had a history of steroid therapy, and two were administered with inhaled steroids.…”
Section: Discussionmentioning
confidence: 59%
“… 5 Oki et al reported a case of M. abscessus nasopharyngitis resulting from the transmission of bacteria from contaminated medical devices that were only washed with tap water, which had been used during repeat nasopharyngeal abrasive therapy for pharyngitis. 12 Our patient had no history of dental or otolaryngological treatments.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations